CCDC88B is required for pathogenesis of inflammatory bowel disease. Issue 1 (December 2017) - Fodil, Nassima; Moradin, Neda; Leung, Vicki; Olivier, Jean-Frederic; Radovanovic, Irena; Jeyakumar, Thiviya; Flores Molina, Manuel; McFarquhar, Ashley; Cayrol, Romain; Bozec, Dominique; Shoukry, Naglaa; Kubo, Michiaki; et al.
Abstract Inflammatory bowel disease (IBD) involves interaction between host genetic factors and environmental triggers. CCDC88B maps within one IBD risk locus on human chromosome 11q13. Here we show that CCDC88B protein increases in the colon during intestinal injury, concomitant with an influx of CCDC88B+ lymphoid and myeloid cells. Loss of Ccdc88b protects against DSS-induced colitis, with fewer pathological lesions and reduced intestinal inflammation in Ccdc88b-deficient mice. In a T cell transfer model of colitis, Ccdc88b mutant CD4+ T cells do not induce colitis in immunocompromised hosts. Expression of human CCDC88B RNA and protein is higher in IBD patient colons than in control colon tissue. In human CD14+ myeloid cells, CCDC88B is regulated by cis-acting variants. In a cohort of patients with Crohn's disease, CCDC88B expression correlates positively with disease risk. These findings suggest that CCDC88B has a critical function in colon inflammation and the pathogenesis of IBD. Hook-related protein family member CCDC88b is encoded by a locus that has been associated with inflammatory bowel disease. Here the authors show that Ccdc88b inactivation in T cells prevents colitis in a transfer model, and detect high colonic levels of CCDC88b in patients with Crohn disease or ulcerative colitis, identifying that expression correlates with disease risk.